Three-dimensional gait analysis of orthopaedic common foot and ankle joint diseases - Wang, Yifan; Qi, Yansong; Ma, Bingxian; Wu, Haihe; Wang, Yongxiang; Wei, Baogang; Wei, Xinghua; Xu, Yongsheng (Frontiers in Bioengineering and Biotechnology, 2024)
Walking is an indispensable mode of transportation for human survival. Gait is a characteristic of walking. In the clinic, patients with different diseases exhibit different gait characteristics. Gait analysis describes the specific situation of human gait abnormalities by observing and studying the kinematics and dynamics of limbs and joints during human walking and depicting the corresponding geometric curves and values. In foot and ankle diseases, gait analysis can evaluate the degree and nature of gait abnormalities in patients and provide an important basis for the diagnosis of patients' diseases, the correction of abnormal gait and related treatment methods. This article reviews the relevant literature, expounds on the clinical consensus on gait, and summarizes the gait characteristics of patients with common ankle and foot diseases. Starting from the gait characteristics of individuals with different diseases, we hope to provide support and reference for the diagnosis, treatment and rehabilitation of clinically related diseases.